Strategi Penganggaran Berbasis Program dan Kegiatan pada Pembangunan Daerah Kabupaten Badung 2022 - I Nyoman Tingkes; I Ketut Sirna (Jurnal Bisnis dan Kewirausahaan, 2023)
This evaluation research aims to analyze the performance achievements of the nine regional development priorities which are translated into programs and activities of basic service obligatory affairs, non-basic service obligatory affairs, and optional affairs. The quantitative data used comes from the District Head's LKPJ 2022. On the other hand, the qualitative data comes from the results of in-depth interviews, focus group discussions, and observations, both direct and indirect. Evaluation analysis techniques include four stages, namely need assessment, program planning, formative evaluation, and evaluation. The results of the study show that the performance achievements are in the good category (83.67 percent). The performance results are determined by institutional, bureaucratic, leadership, and strategic factors. Based on these findings, it can be suggested that (a) adequate technical guidelines for the implementation of programs and activities be issued, (b) communication, information, and education on the provisions of the rules that serve as a reference for the implementation of programs and activities to be carried out more intensively, (c) the competency of ASN is continuously improved continuous, planned and integrated, (d) aspects of IQ in the form of vision, PQ in the form of work discipline, EQ in the form of passion and SQ aspects in the form of awareness of conscience need attention in placing leadership positions, and (e) vision and goals Organizations need to be revitalized continuously and adapted to the results of external and internal environmental analysis, and developments in science and technology.